Cliques, Clans, Community, and Competence: The Experiences of Students with Behavioral Disorders in Rural School Systems - Lisa A. Bloom; John Habel (Journal of Research in Rural Education, 1998)
A romantic vision ofruralness persists in the minds ofmany, but it appears that living in a small rural community may not be an advantage for children and youth with, or at riskfor, behavioral disorders. Recent social constructivist thought stands in contrast to the prevailing view that the cognitive and the social can be studied independently. In this study we bring this social dimension ofschool to bear on the efforts ofstudents with and at riskfor behavioral disorders to acquire competence. An analysis of the descriptions of 39 students concerning their experiences in schools in a rural region of western North Carolina revealed two major themes: "community," with its components, relationships with peers, relationships with teachers, social isolation, creating community, and distorted belonging; and "competence, .. with its components, schools' contribution to incompetence, the dilemma ofrural schools in encouraging competence, and encouraging competence. In order to reflect the richness and coherence of the students' accounts, results are presented using direct quotes and discussed within the context of current thought about social constructivism and research in behavioral disorders and rural education.